New proposed drift limit states for box-type structural systems considering local and global damage indices. Issue 15 (November 2019) - Mohsenian, Vahid; Mortezaei, Alireza
The maximum displacement responses under the seismic motions are usually considered as an indicator for damage evaluation. It is obvious that appropriate selection of drifts corresponding to various damage levels plays an important role in safety and economy of a design project. Despite the extensive use of the box-type structural system in mass construction and housing industry, there is no special design requirement for this structural system. Due to three-dimensional behavior and interaction of intersecting walls and slabs, it is expected that this system presents different seismic performance in comparison to the conventional shear wall buildings. This study evaluates the overall and story failure mechanism as well as global and local damage indices in this structural system. Maximum allowable drift ratios of 0.45%, 0.65%, and 0.8% are suggested for the immediate occupancy, life safety, and collapse prevention levels, respectively. Moreover, a damage index based on the maximum relative inter-story drifts is proposed to assess the failure in the height domain. According to the assessments, the story and global failure occurring due to considerable damages in main load bearing elements reveals high importance of local damage indices in box-type structural system. Based on the results, it is concluded that the proposed maximum values for drifts in different standards and codes are not reliable. Considering the shear-control behavior and depending on the expected performance levels, the proposed local damage indices are considered as accurate control indicators for box-type structural system.